Microbiome Variation Across Populations of Desert Halophyte Zygophyllum qatarensis - Khan, Abdul Latif; Lopes, Lucas Dantas; Bilal, Saqib; Asaf, Sajjad; Crawford, Kerri M.; Balan, Venkatesh; Al-Rawahi, Ahmed; Al-Harrasi, Ahmed; Schachtman, Daniel P. (Frontiers in Plant Science, 2022)
Microbial symbionts play a significant role in plant health and stress tolerance. However, few studies exist that address rare species of core-microbiome function during abiotic stress. In the current study, we compared the microbiome composition of succulent dwarf shrub halophyte Zygophyllum qatarensis Hadidi across desert populations. The results showed that rhizospheric and endosphere microbiome greatly varied due to soil texture (sandy and gravel). No specific bacterial amplicon sequence variants were observed in the core-microbiome of bulk soil and rhizosphere, however bacterial genus Alcaligenes and fungal genus Acidea were abundantly distributed across root and shoot endospheres. We also analyzed major nutrients such as silicon (Si), magnesium, and calcium across different soil textures and Z. qatarensis populations. The results showed that the rhizosphere and root parts had significantly higher Si content than the bulk soil and shoot parts. The microbiome variation can be attributed to markedly higher Si – suggesting that selective microbes are contributing to the translocation of soluble Si to root. In conclusion, low core-microbiome species abundance might be due to the harsh growing conditions in the desert – making Z. qatarensis highly selective to associate with microbial communities. Utilizing rare microbial players from plant microbiomes may be vital for increasing crop stress tolerance and productivity during stresses.